Drying, Roasting, and Calcining of Minerals - Battle, Thomas; Downey, Jerome; May, Lawrence; Davis, Boyd.; Neelameggham, Neale; Sanchez-Segado, Sergio; Pistorius, Chris; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The papers in this volume give the reader focused information on the important extractive metallurgy unit operations of drying, roasting, and calcining.
Keywords: Metals; Materials; Materials -- Analysis; Metals and Alloys; Materials Engineering; Characterization and Analytical Technique